A comparison of different cryoprotectant solutions and thawing methods for cryopreservation of embryos of mice and rats - T. N. Igonina; E. Yu. Brusentsev; I. N. Rozhkova; V. A. Naprimerov; S. Ya. Amstislavsky (Вавиловский журнал генетики и селекции)
The proper choice of cryoprotectant and thawing method affects cryopreservation efficiency. A freezing-thawing method for sparing embryonic cells was evaluated in experiments with ICR mice. Cleavage-stage embryos of ICR mice, GC rats, and OXYS rats were collected on Day 3 of pregnancy and frozen in plastic straws according to a standard protocol. Permeating (ethylene glycol and glycerol) and nonpermeating (sucrose) cryoprotectants and their combinations were compared during the freezing of ICR mouse embryos. With these mice, two thawing methods were compared: rapid (water bath, 10 s, 37 °С) and slow (40 s, room temperature; 40 s, 30 °С). Embryo viability in mice and rats was evaluated by their in vitro culturing after thawing. Our data on mice indicate that slow thawing is more suitable for sparing the integrity of embryonic cells; moreover, supplementation of the main cryoprotectant (either ethylene glycol or glycerol) with sucrose is beneficial for subsequent in vitro culture, especially in the case of glycerol. This freezing-thawing protocol (with glycerol and sucrose as cryoprotectant agents and slow thawing) was applied to rats of the GC and OXYS strains; the survival rate after cryopreservation was 68–83.3 %, and the rate of in vitro development was 64.7–66.6 %.